RISK FACTORS FOR PRIMARY LIGHT ATELEKTASIS IN NEWBORN - Zebo I. Ruzieva; Feruza M. Nuriddinova (Scholar Express Journals, 2024)
In this study, the frequency of occurrence of risk factors and the pathogenetic mechanism of primary atelectasis of the lung in premature and full-term children were studied. Studied 98, including 52 premature, 46 full-term, clinical and anamnestic data and risk factors for primary atelectasis of the lung. The results showed that maternal diseases such as preeclampsia, infectious diseases, endocrine pathology and various extragenital diseases, as well as complications associated with the birth process, are risk factors for varying degrees of development of primary pulmonary atelectasis in newborns. As risk factors, the age of the mother under 20 and over 35 years, preeclampsia, infectious diseases, complications of childbirth, TBI in a child, and a high level of congenital malformations were identified. It was noted that primary atelectasis of the lungs in most cases occurs in premature babies, and the rate of development of diseases classified as risk factors is also high.
Keywords: Child; lung atelectasis; preterm birth